Channel Modification Engineering by Plasma Processing in Tin-Oxide Thin Film Transistor: Experimental Results and First-Principles Calculation - Chiu, Y. C.; Chen, P. C.; Chang, S. L.; Zheng, Z. W.; Cheng, C. H.; Liou, G. L.; Kao, H. L.; Wu, Y. H.; Chang, C. Y. (My University, 2017)
In this paper, we investigated the effects of oxygen plasma treatment on tin oxide (SnOx) thin film transistors (TFTs). By using oxygen plasma treatment on SnOx active channel layer, excess oxygen was incorporated to the channel layer and converted oxygen-deficient SnOx to oxygen-rich SnO2-x, which in turn causes the device operation from p-type to n-type. Tuning the different exposure time of oxygen plasma, the optimal TFT device exhibits n-type properties with an on/off current ratio of 2.6 x 10(4), a very high field-effect mobility of 89 cm(2) V-1 s(-1), and a threshold voltage of -0.95 V. Furthermore, the effects of oxygen plasma treatment on band structure, density of states and electron density difference of the SnOx channel layer were performed by the first-principles calculation using density functional theory. The results show that the oxygen plasma treatment approach has high potential for high-performance TFT applications. (C) 2017 The Electrochemical Society. All rights reserved.